Description of the profile of the population insured in the AFPs, which allows determining their dissociation in the construction of a general mortality table - Infante Rojas, Magen Danielle (2016)
In the midst of the public debate regarding the comparison of official INEI data and data processed by the SBS in the construction of a new mortality table, the argument arose that the SBS needs only data from policyholders belonging to pension fund insurers as sufficient to construct a general mortality table. Due to this scenario, a set of characteristics of policyholders in the AFPs (from the ENAHO database) is contextualized in order to determine their influence on the construction of a general mortality table. To this end, the characteristics of the population affiliated with the private pension system (AFP) were examined with respect to the population affiliated with the public pension system (ONP) and the non-affiliated population. Differences were found in the characteristics that determine the mortality experience of these populations. Therefore, it is concluded that a mortality table based on the mortality experience of the population affiliated to the AFP is not linked to the mortality tables of the other populations.